2018
DOI: 10.1002/hed.25537
|View full text |Cite
|
Sign up to set email alerts
|

Association between loss of Y chromosome and poor prognosis in male head and neck squamous cell carcinoma

Abstract: Background Head and neck squamous cell carcinoma (HNSCC) is more prevalent in men than women and this disparity cannot be fully explained by known risk factors. Recent studies have shown that loss of Y chromosome (LoY) confers an increased risk of solid cancer and reduces life expectancy in men. Methods Using publicly available data from The Cancer Genome Atlas, we investigated the prevalence of LoY and its association with clinicopathological features in male HNSCC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 51 publications
(102 reference statements)
5
29
0
Order By: Relevance
“…The Y chromosome evolved to retain genes with male-specific functions, as well as genes widely expressed involved in regulation of transcription, translation, and protein stability (36). Age-related loss of the Y chromosome in peripheral blood cells is a common somatic event in males and may be associated with higher risk of cancer, including leukemia, breast, and head and neck (37)(38)(39)(40).…”
Section: Sex Differences In Genetics Sex Chromosomesmentioning
confidence: 99%
“…The Y chromosome evolved to retain genes with male-specific functions, as well as genes widely expressed involved in regulation of transcription, translation, and protein stability (36). Age-related loss of the Y chromosome in peripheral blood cells is a common somatic event in males and may be associated with higher risk of cancer, including leukemia, breast, and head and neck (37)(38)(39)(40).…”
Section: Sex Differences In Genetics Sex Chromosomesmentioning
confidence: 99%
“…Further, the extremely high frequency of >50% of LoY suggests that there is a fitness advantage. To our knowledge, EAC represents the highest rate of LoY among solid tumors [ 15 , 24 , 25 , 26 ]. Cestari et al found LoY in high grade dysplastic Barrett’s mucosa but not yet in low grade dysplastic or normal Barrett’s mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…DNA FISH in cell lines was performed and quantified by the WVU Cytogenetics Laboratory. DNA FISH for the tissue arrays was performed as described previously with the following modifications (21). Slides were first baked at 60 C before proceeding through the protocol.…”
Section: Dna Fish and Tissue Array Analysismentioning
confidence: 99%
“…21, 34-41). LOY involves the loss of the entire Y chromosome and occurs in human male tissues as a consequence of aging; however, only recent studies have begun validating a correlation between LOY and cancer biology (18,21,(36)(37)(38)(40)(41)(42)(43)(44). Using DNA-FISH, we investigated the sex chromosome status of our panel of cell lines.…”
Section: Loss Of the Linc-spry3 Transcripts In The Radioresistant Celmentioning
confidence: 99%